Effects of Extraction Temperature on the Total Protein and Vitamin C Levels of Channa striata Water Extract - Restiasari, Anggi; Aulifa, Diah Lia; Febrianti, Raden Maya; Rosdianto, Aziiz Mardanarian; Rukayadi, Yaya; Levita, Jutti; Diantini, Ajeng (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Channa striata are a freshwater fish, popularly known as snakehead fish in Indonesia, belonging to the family Channidae. The fish are usually consumed for their protein and their medicinal properties in treating wounds and pain. Previous study showed that the protein in C. striata can be extracted using water at 50 °C for 60 minutes, and using acetone at 4°C for 24 hours. Considering all, this work aims to investigate the effects of temperature on the protein and vitamin C content of the water extract from C. striata fish collected in Rancaekek, West Java. The meat was extracted with water at 55-60 °C for 10 and 30 minutes, compared to the cold extraction at room temperature for 60 minutes. The resulting extracts were subjected to the qualitative Biuret color test and quantitative protein analysis using the Kjeldahl Method. The study revealed that cold extraction of C. striata meat for 60 minutes resulted in the highest protein content (0.29% in the residue and 0.35% in the supernatant). Moreover, the vitamin C levels, determined using the iodometric method, in the homogenate, supernatant, and residue were 60.64 mg/100 g, 60.82 mg/100 g, and 43.38 mg/100 g respectively.